Kinerja Persimpangan Jalan Emmy Saelan – Jalan Maluku, Jalan Wolter Monginsidi – Jalan Tj. Karang dan Jalan Emmy Saelan – Jalan Tj. Manimbaya - I. Ismadarni; M. Sutrisno; S.P. Lestari; R. Rochmad (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
The purpose of this study is to determine the performance of intersections and provide solutions to problems that occur at the intersection of Emmy Saelan – Maluku street, and Wolter Monginsidi street – Tj. Karang street and Emmy Saelan street – Tj. Manimbaya street. The analysis included road performance, existing conditions and predictions over the next 5 years by calculating the average crossing delay based on the Indonesian Road Capacity Manual (MKJI)1997. From the results of research on the existing conditions DS = 1.24 crossing delay of Emmy Saelan street – Maluku street 55,89 det/smp that is in LOS E, intrection of Wolter Monginsidi – Tj. Karang street value of DS = 1.09 and corssing delay = 24.32 det/smp that is in LOS C and intersection of Emmy Saelan street – Tj. Manimbaya value of DS = 1.06 and crossing delay = 22.60 det/smp that is in LOS C. So it requires handling of the problem of intersections in the future, the first solution is to make the road median from intrection service levelof W. Monginsidi street – Tj. Karang street up to intrection of Emmy Saelan street – Anoa II street, with a median opening at the point before the bridge. Value of DS = 0.57 dan crossing delay of Emmy Saelan street – Maluku street = 10,16 det/smp that is in LOS B, intrection of Wolter Monginsidi street – Tj. Karang street value of DS = 0.76 dan crossing delay = 12.29 det/smp that is in LOS B and intrection of Emmy Saelan – Tj. Manimbaya street value of DS = 0.41 and crossing delay = 8.12 det/smp that is in LOS B.